Ketahanan Nasional Menghadapi Ancaman Lone Wolf Terrorism Di Jawa Barat - Tiara Firdaus Jafar; Arfin Sudirman; Affabile Rifawan (Universitas Gadjah Mada, 2019)
ABSTRACTWest Java had been considered as the most vulnerable area for the spread of radicalism in Indonesia, its presence brought new threats which were considered more difficult to detected than a network of structured terrorism organizations. This article emphasized the issue of lone wolf terrorism and the history of its development from structured terrorism organizations in West Java.By using 4 typologies proposed by Raffaello Pantucci namely loner, lone wolf, lone wolf pack and lone attacker this article concluded that the occurrence of a network-based terrorism movement or Transnational Organized Crime to Lone Wolf Terrorism in West Java was the same pattern carried out in conflict areas in Iraq and Syria. This was caused by the disconnection of structural-organizational communication between its members and recruiting process was conducted randomly.ABSTRAK Jawa Barat telah dianggap sebagai daerah paling rawan penyebaran paham radikalisme di Indonesia, kehadirannya membawa ancaman baru yang dinilai lebih sulit untuk dideteksi daripada jaringan organisasi terorisme terstruktur. Artikel ini menekankan pada isu lone wolf terrorism dan sejarah perkembangannya dari organisasi terorisme terstruktur di Jawa Barat.Dengan menggunakan 4 tipologi yang dikemukakan oleh Raffaello Pantucci yakni loner, lone wolf, lone wolf pack dan lone attacker artikel ini menyimpulkan bahwasanya terjadinya pergeseran gerakan terorisme berbasis jaringan atau Transnational Organized Crime ke Lone Wolf Terrorism di Jawa Barat merupakan pola yang sama dilakukan di daerah konflik di Irak dan Suriah. Hal tersebut disebabkan oleh diputuskannya komunikasi struktural-organisasional antar anggotanya serta perekrutan dilakukan secara acak.